2018
DOI: 10.15653/tpg-170491
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications in equine elective, clean orthopaedic surgery with/without antibiotic prophylaxis

Abstract: Summary Objective: Retrospective analysis of postoperative complications in equines after clean, orthopaedic surgical procedures in order to detect differences between animals treated with antibiotics and horses without receiving these drugs. Material and methods: Details on 652 patients, surgical procedures and surgery-associated complications were compiled from horses being operated between June 2011 and January 2015. Antibiotic-receiving patients (n = 259) were tested for differences in complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In splint bone removal, complications occur rarely and include: infection of the subcutaneous tissue; periosteal proliferative changes; and exuberant callus, which may affect the suspensory ligament [36]. In spite of preserving aseptic conditions during surgery and the experience of the surgeons, complications occurred in 6% (swelling and exudation was excluded) of the cases undergoing arthroscopy [2]. In the current study, a complication was detected (patient A27) in one case (2.44%) based on clinical signs and the APPs' measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In splint bone removal, complications occur rarely and include: infection of the subcutaneous tissue; periosteal proliferative changes; and exuberant callus, which may affect the suspensory ligament [36]. In spite of preserving aseptic conditions during surgery and the experience of the surgeons, complications occurred in 6% (swelling and exudation was excluded) of the cases undergoing arthroscopy [2]. In the current study, a complication was detected (patient A27) in one case (2.44%) based on clinical signs and the APPs' measurements.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated risk of surgical site infection [1] occurs during arthroscopic removal of large osteochondral fragments and may lead to septic arthritis. The risk of postoperative complications after clean orthopedic surgery [2] as well as joint infection after arthroscopy [3] is comparable when no antimicrobials or pre-/perioperative antimicrobial therapy has been applied. In horses, the APR is manifested in a variety of physiological processes in conditions of excessive stress induced by transport and physical exercise, and this emphasizes the role of APP as an important biomarker in horses [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, in the latter study by Olds et al (2007), there was no significant difference in synovial sepsis incidence between horses receiving and not receiving SAP. Horses undergoing a variety of elective, clean orthopaedic surgical procedures (arthroscopy, fasciotomy, splint bone removal, tenotomy, neurectomy, tenoscopy/bursoscopy or a combination) had an overall complication rate of 39% (255/652) with complications not being significantly different between horses receiving SAP (97/259, 38%) and not receiving SAP (159/393, 40%, Stöckle et al, 2018). In the latter study, 2.5% (5/198) of horses receiving SAP and 0.7% (2/265) of horses not receiving SAP developed septic arthritis.…”
Section: Basics Of Sapmentioning
confidence: 99%
“…(Borg & Carmalt, 2013) No evidence across human or veterinary medicine supports the use of antimicrobial prophylaxis in clean, clean-contaminated or contaminated procedures beyond the perioperative period. (Borg & Carmalt, 2013;Bratzler et al, 2013;Brunsting et al, 2018;Southwood, 2014;Stockle et al, 2018) However, despite the previously reported low rate of septic synovitis following elective arthroscopy and the fact that Gram-positive bacteria are most commonly isolated in cases of septic synovitis, (Brunsting et al, 2018) equine surgeons often use empiric broad-spectrum antimicrobial therapy, at times with prolonged post-operative administration. (Muntwyler et al, 2020) Variability in antimicrobial regimes reflects the overall lack of usage guidelines in horses for specific procedures, suggesting that clinician preference and previous training strongly affect practices.…”
Section: Introductionmentioning
confidence: 99%